The Influence of Exercise Methods and Eye-Foot Coordination on the Smash Ability of Volley Ball Athletes - Dwi Maya Abdiliah; Willadi Rasyid; Syafruddin (Gladi : Jurnal Ilmu Keolahragaan, 2022)
This article aims to determine the effect of extensive and intensive interval training methods and eye-foot coordination on the smash ability of volleyball athletes. This type of research uses a quasi-experimental method using treatment with a Level 2 x 2 design. The sample in this study was male volleyball athletes from the Riau Province Sports High School, amounting to 28 people. Ankle coordination test using Soccer Wall Volley test, and smash ability using smash skill test. The results showed 1) there was a difference in the effect of the extensive interval training method and the intensive interval training method on smash ability where Fh 47.14 > Ft 3.01. 2) there is an interaction between the exercise method and ankle coordination seen from Fh 24 > Ft 3.01. 3) In high category eye-foot coordination, extensive interval training method is better than intensive interval training method to improve smash ability as seen from Qcount 11.36 > Qtable 3.34. 4) There is no difference in the effect of low eye-foot coordination between the intensive training method and the extensive interval method on increasing smash ability, it can be seen from Qcount 2.60 < Qtable 3.34.